The Empowerment of Integrated Development Post of Non-Communicable Diseases in Efforts to Prevent and Control Non- Communicable Diseases - Yandrizal Yandrizal; Rizanda Machmud; Melinda Noer; Hardisman Hardisman; Afrizal Afrizal; Nur Indrawati Lipoeto; Ekowati Rahajeng; P.A Kodrat Pramudho (Intelektual Pustaka Media Utama, 2016)
Non-Communicable disease has already been the main cause of death in many countries, as many as 57 million death in the world in 2008, 36 million (63 percent) is because of un-infectious disease, specifically heart illness, diabetes, cancer, and chronic respiratory diseases. Prevention and controlling efforts of un-infectious diseases developing in Indonesia is non-communicable disease integrated development post (Pospindu PTM). This research used combination method approach with exploratory design. Exploratory design with sequential procedure used combination consecutively, the first is qualitative and the second is quantitative method. Public Health Center formed Posbindu PTM has not disseminate yet to all stakeholders. Posbindu PTM members felt benefit by following this activity. Some of them did not know follow the activity because of unknown about it. There was connection between coming behavior to Posbindu PTM to preventing behavior of non-communicable disease.Percentage for high blood pressure risk indicated 20-25 percent from all visitors. Formulation of its policy implementation started with stakeholder analysis; head of sub district, head of urban village, head of health department in regency/city, head of public health service, head of neighborhood Association, and the head of family welfare development. Analysis of perception, power and authority found that every stakeholder had authority to manage the member directly or indirectly. It was not implemented because of the lack knowledge of stakeholders about the Posbindu PTM function.They would play a role after knowing the aim and advantage of the post by motivate the people to do early detection, prevention and control the non-communicable disease. The members were given wide knowledge about early detection, preventing and control the un-infectious disease, measuring and checking up their healthy continuously so that keep feeling the advantage of coming to the post.